Prevalence of dysmenorrhoeal pain and its impact on school performance: A cross-sectional study - Magar, Ashmita Thapa; Alam, Nazmul (Recent Research in Science and Technology, 2020)
BangladeshABSTRACTMenstruation is normal biological phenomena for girls and women. During menstruation, girls and women feel a certain degree of pain (dysmenorrhea) that can be minor to severe resulting obstacles in carrying daily life activities including school. This study was conducted to determine how dysmenorrheal pain has affected the students’school as well as daily life along with prevailing social and cultural norms during menstruation. Following a cross-sectional design, this study took place among 366 students of Kathmandu (66.1%) and Dhading (33.9%) in Nepal of aged from 13 to 20 years. Of all the samples, 89% of the students complained of having dysmenorrhea where moderate degree of pain had the highest frequency of 49.7%. Nonetheless of the degree of pain, 45.1% missed school because of it. Besides missing classes, 81% didn’t participate in sports activities during their period. 38% students regularly followed restrictions applied during period while 34% followed them sometimes only. 83% complained about school administration failing to address periodic problems. I would recommend the school administration to have an infirmary where the students can take rest and continue their classes after that. Adding on to it, the administration should be able to provide emergency sanitary pads and heat pads, so that the students dont have to go back home and miss their classes.